Analisis Manajemen Risiko Tingkat Suku Bunga pada UMKM Pengguna Kredit Usaha Rakyat (KUR): (Studi Pada Depot Air Minum Kari Water Kecamatan Kulim Kota Pekanbaru) - Umi Solehah; Emi Vita Lina; Sri Cahyani; Oktaviana Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze interest rate risk management in Micro, Small, and Medium Enterprises (MSMEs) that use People's Business Credit (KUR) facilities, with a case study at the Kari Water Drinking Water Depot in Kulim District, Pekanbaru City. Fluctuations in interest rates are one of the financial risks that can affect the continuity of MSME businesses, especially in terms of the ability to pay credit obligations. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the Kari Water Depot faces financial risks due to interest rate fluctuations, operational risks related to water distribution and quality, and legal risks due to drinking water quality regulations. The application of risk management based on ISO 31000 has been proven to help in the process of systematic risk identification, analysis, and mitigation. The mitigation strategy through investment in Reverse Osmosis (RO) technology is considered effective because it can improve product quality and operational efficiency. However, the success of this strategy is greatly influenced by the readiness of human resources, access to financing, and mature risk planning. This study recommends the importance of risk management training for MSMEs and policy support in the form of access to affordable funding and environmentally friendly technology to improve the competitiveness and sustainability of MSMEs amidst economic dynamics.